Polymetallic nodules are essential for food-web integrity of a prospective deep-seabed mining area in Pacific abyssal plains - Stratmann, Tanja (Sci Rep, 2021)
Polymetallic nodule fields provide hard substrate for sessile organisms on the abyssal seafloor between 3000 and 6000 m water depth. Deep-seabed mining targets these mineral-rich nodules and will likely modify the consumer-resource (trophic) and substrate-providing (non-trophic) interactions within the abyssal food web. However, the importance of nodules and their associated sessile fauna in supporting food-web integrity remains unclear. Here, we use seafloor imagery and published literature to develop highly-resolved trophic and non-trophic interaction webs for the Clarion-Clipperton Fracture Zone (CCZ, central Pacific Ocean) and the Peru Basin (PB, South-East Pacific Ocean) and to assess how nodule removal may modify these networks. The CCZ interaction web included 1028 compartments connected with 59,793 links and the PB interaction web consisted of 342 compartments and 8044 links. We show that knock-down effects of nodule removal resulted in a 17.9% (CCZ) to 20.8% (PB) loss of all taxa and 22.8% (PB) to 30.6% (CCZ) loss of network links. Subsequent analysis identified stalked glass sponges living attached to the nodules as key structural species that supported a high diversity of associated fauna. We conclude that polymetallic nodules are critical for food-web integrity and that their absence will likely result in reduced local benthic biodiversity.